Dietary β-hydroxybutyric acid improves the growth performance of young ruminants based on rumen microbiota and volatile fatty acid biosynthesis - Chai, Jianmin; Liu, Zeyue; Wu, Jun; Kang, Yuan; Abdelsattar, Mahmoud M.; Zhao, Wei; Wang, Shiqin; Yang, Shuli; Deng, Feilong; Li, Ying; Zhuang, Yimin; Zhang, Naifeng (Frontiers in Microbiology, 2024)
The ketone body β-hydroxybutyric acid (BHB) plays critical roles in cellular proliferation and metabolic fuel utilization; however, its effects on the rumen microbiota remain unknown. Here, three doses of BHB (low, medium and high) were supplemented to early-weaned goat kids.Compared to controls, the beneficial effects of BHB on growth and rumen development were observed in goats at 90 days of age (d). The low dose of dietary BHB increased the concentration of rumen acetate, propionate and butyrate on d90. The sequencing results of the rumen microbiota revealed marked shifts in rumen microbial community structure after early weaned goat kids consumed two-month BHB feeding. The signature bacterial ASVs for each treatment were identified and were the main drivers contributing to microbial interactions in the rumen.The bacteria associated with rumen weight were also correlated with body weight. Some classified bacterial signatures, including Prevotella, Olsenella umbonate and Roseburia faecis, were related to rumen volatile fatty acids and host development. Overall, dietary BHB altered the rumen microbiota and environments in young goats, which contributed to rumen development and growth.